Coordination of muscle maintenance and innate immunity through integrated tissue physiology in Drosphila - Green, Nicole Marie (Kansas State University, 2018)
Maintenance of muscle tissue during development is greatly dependent upon the extracellular matrix (ECM) to stabilize, sense, and compensate for changes in the local environment. Muscle has a particularly high demand for a dynamic ECM to allow for contraction and to transmit forces necessary for generating movement. Inefficient contraction and/or detachment can lead to muscle tissue damage and the release of damage-associated molecular patterns (DAMPs), which overactivate immune responses and drive the progression of muscle diseases. Our lab uses the Drosophila muscle attachment site (MAS) as a model to characterize novel genes and mechanisms involved in muscle maintenance. Initially, we were focused on characterizing a novel ECM protein, Fondue (Fon), which had previously been shown as a critical mediator of ECM stability in the hemolymph clot. Mutations in fon and the knockdown of fon through RNAi causes body wall muscles to detach and also creates large gaps between muscle hemisegments. TEM analysis of fon mutant MASs revealed a loss of ECM integrity and important support features including disruption of cuticle and tendon architectures, a lack of muscle-tendon interdigitation, and a loss of electron-dense matrix accumulation. More interestingly, a sensitized background screen revealed a subset of coagulation proteins, fon, Tiggrin, and Lsp1γ, that were necessary for stabilizing muscle attachment sites. Further investigation into gene expression profiles of mutants experiencing hypercontraction-induced muscle tissue stress indicated a clear trend of innate immune activation, suggesting a broader connection between muscle development and innate immunity. In fon mutants with muscle detachment, we also observe abnormal melanin accumulation as melanotic tumors or along the larval MASs, activation of Toll signaling in the fat body, and constitutive expression of the antimicrobial peptide (AMP), drosomycin. In a fon-sensitized background assay, we identified genetic interactions between fon and Toll pathway members, including the NFκB inhibitor/IκB, cactus. At the local level, fon-mediated muscle detachment and muscle hypercontraction mutants, Mhc[superscript S1] and Brkd[superscript J29], cause JAK/STAT activation within muscle tissue. We propose a model where muscle tissue stress caused by disruptions to muscle homeostasis progresses muscle disease through overactivation of the innate immune system. Understanding the mechanisms by which these two biological processes are intertwined will advance our knowledge of how tissue stresses can be sensed and elicit multi-tissue responses.
Keywords: Muscle; Innate immunity; Drosophila; Tissue maintenance